2008
DOI: 10.1080/13647830701716948
|View full text |Cite
|
Sign up to set email alerts
|

Combustion waves in a model with chain branching reaction and their stability

Abstract: In this paper the travelling wave solutions in the adiabatic model with two-step chain branching reaction mechanism are investigated both numerically and analytically in the limit of equal diffusivity of reactant, radicals and heat. The properties of these solutions and their stability are investigated in detail. The behaviour of combustion waves are demonstrated to have similarities with the properties of nonadiabatic one-step combustion waves in that there is a residual amount of fuel left behind the travell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
2
21
1
Order By: Relevance
“…The properties of the travelling combustion waves were investigated analytically by Dold (2007), Gubernov et al (2008a) and numerically by solving the set of equations (3.1) subject to boundary conditions (3.2) by Gubernov et al (2008aGubernov et al ( , 2009. It was found that varying the Lewis number for fuel, L A , has a substantial effect on the properties of the premixed flames, whereas the variation of Lewis number corresponding to the radicals, L B , affects only quantitative behaviour of the combustion waves.…”
Section: Properties Of the Travelling Wave Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of the travelling combustion waves were investigated analytically by Dold (2007), Gubernov et al (2008a) and numerically by solving the set of equations (3.1) subject to boundary conditions (3.2) by Gubernov et al (2008aGubernov et al ( , 2009. It was found that varying the Lewis number for fuel, L A , has a substantial effect on the properties of the premixed flames, whereas the variation of Lewis number corresponding to the radicals, L B , affects only quantitative behaviour of the combustion waves.…”
Section: Properties Of the Travelling Wave Solutionmentioning
confidence: 99%
“…In the product region, the reaction must be completed; therefore, the branching term is less than the recombination term in the third equation of equation (2.1), that is r > s exp(−1/u b ). This condition was first derived in Gubernov et al (2008a) for the adiabatic case and defines the region in the parameter space, where the travelling combustion waves exist. Once this condition is violated the adiabatic combustion waves exhibit extinction.…”
Section: Properties Of the Travelling Wave Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gubernov and coworkers [16,17,18,19] use another choice of scalings. The relationships between their dimensionless space and time scales (denoted by a "G" subscript) and those used here are…”
Section: Introductionmentioning
confidence: 99%
“…As for the one-step model, he found that the only qualitative difference from the CDM results is that the flame remains unstable to a long-wavelength hydrodynamic instability, even for Lewis numbers of the fuel above the critical value for purely thermal-diffusive induced instability. Gubernov and coworkers [16,17,18] then examined the linear stability of the two-step model for finite activation energies (i.e., without invoking the HAEA approximation) in the context of the CDM. They considered only one-dimensional perturbations corresponding to a purely longitudinal pulsating instability.…”
Section: Introductionmentioning
confidence: 99%